Method for producing partially sulfonated polyphenylene sulfone, and PEM film assembly having a catalyst coating film.

JP2026534526APending Publication Date: 2026-10-16SIEMENS ENERGY GLOBAL GMBH & CO KG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2026519429
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-02
Filing Date
2024-09-02
Publication Date
2026-10-16

Smart Images

  • Figure 2026534526000001_ABST
    Figure 2026534526000001_ABST
Patent Text Reader

Abstract

The present invention relates to a method (100) for producing a reagent for the partial sulfonation of polyphenylene sulfone, comprising the steps: S1: introducing polyphenylene sulfone into sulfuric acid to at least the solubility limit and S2: separating undissolved components to obtain the reagent. The present invention further relates to a method for producing a partially sulfonated polyphenylene sulfone (1), a method (400) for producing a catalyst coating film (10) for an electrochemical cell, and a PEM film assembly having the catalyst coating film (10).
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present invention relates to a method for producing a reactant for partial sulfonation of polyphenylene sulfone, a method for producing partially sulfonated polyphenylene sulfone, a method for producing a catalyst coating film for an electrochemical cell, a PEM membrane assembly having the catalyst coating film, an electrolysis cell, a cell stack, and an electrolysis installation.

[0002] Hydrogen can be produced by water electrolysis, and various technologies can be used. A technically already industrially established technology is polymer electrolyte membrane water electrolysis (PEMWE). Here, the polymer electrolyte membrane is the core element, which is currently based on perfluorinated ionomers. Ionomers are polymers having ionic groups, whereby the ionomers have the property of proton conductivity. In addition to the membrane, the components of the electrodes currently also consist of fluorinated polymers.

[0003] All fluorinated polymers that have been used in PEMWE to date belong to PFAS (perfluoroalkyl substances and polyfluoroalkyl substances), which, for reasons of health protection and environmental protection by the European Chemicals Agency ECHA, will be completely banned after 2025, or can only continue to be used under strict exception provisions over a transition period that has not yet been defined. Accordingly, there is a need to develop fluorine-free ionomers that can be used as alternative materials to the previous fluoropolymers in electrodes and / or membranes in order to improve environmental and health protection and comply with the modified legal framework.

[0004] For example, a film made from sulfonated polyphenylene sulfone (SPPSU) is known from "High ionic exchange capacity polyphenylensulfone (SPPSU) and polyethersulfone (SPES) crosslinked by annealing treatment: Thermal stability, hydration level and mechanical properties" (J. Mem. Sci. 2010, Vol. 354, pp. 134-141). A method for producing SPPSU by dissolving polyphenylene sulfone (PPSU) in 96% sulfuric acid at 50°C is disclosed. Subsequently, the solution was transferred to ice water, where a white solid precipitated, which was filtered, washed with cold water, and neutralized. The resulting SPPSU was then dried at room temperature under vacuum. To obtain a film, the dried SPPSU was dissolved in dimethyl sulfoxide, poured into a Petri dish, and dried at 120°C for 16 hours. The resulting film was peeled from the Petri dish and dried further under vacuum at 80°C for 24 hours, followed by heating to 170°C to crosslink it. [Prior art documents] [Non-patent literature]

[0005] [Non-Patent Document 1] DI VONA, ML, SGRECCIA, E., TAMILVANAN, M., KHADHRAOUI, M., CHASSIGNEUX, C., KNAUTH, P. High ionic exchange capacity Polyphenylensulfone (SPPSU) and polyethersulfone (SPES) crosslinked by annealing treatment: Thermal stability, hydration level and mechanical properties. J. Mem. Sci. 2010, Vol. 354, S. 134 - 141

[0006] However, the inventors of the present invention found that the yield of partially functionalized SPPSU in production by this method was low, and therefore the described method is unsuitable for large-scale industrial use.

[0007] Experiments are known in which a film is fabricated using SPPSU contained in the liquid phase after separating the water-soluble fraction, i.e., the insoluble fraction, of the reaction product of the reaction between PPSU and concentrated sulfuric acid. This is likely highly functionalized SPPSU. However, this is readily water-soluble and highly sensitive to hydrolysis. Highly functionalized SPPSU can be further processed into a film, but it is essential to stabilize it by cross-crosslinking afterward to reduce water solubility and hydrolysis sensitivity. However, investigations by the inventors of this invention have shown that even if possible, sufficient long-term stability cannot be achieved, especially at higher temperatures, even with post-processing cross-crosslinking.

[0008] Against this backdrop, the object of the present invention is to provide the possibility of obtaining partially sulfonated PPSU in high yield, which can be used for purposes such as manufacturing membranes and / or electrodes for water electrolysis.

[0009] This problem is solved by the subject matter of the independent claim. The dependent claim relates to an embodiment.

[0010] A first aspect of the present invention relates to a method for producing a reactant (German: Reaktant; substance used in a reaction, reaction composition) for the partial sulfonation of polyphenylene sulfone (CAS number 25608-64-4). Partially sulfonated polyphenylene sulfone (partially sulfonated PPSU) can be understood as a sulfonated PPSU having an ion exchange capacity of less than 1 mmol / g, preferably less than 0.5 mmol / g, more preferably less than 0.2 mmol / g, for example less than 0.1 mmol / g, or even less than 0.05 mmol / g. The ion exchange capacity can be determined by acid-base titration.

[0011] The proposed method comprises the following steps: introducing polyphenylene sulfone (PPSU) into sulfuric acid, preferably concentrated sulfuric acid, in a proportion of 96% to 98% by weight in an aqueous solution, to at least the solubility limit, and separating the undissolved components to obtain a reactant.

[0012] The resulting reagent can later be used to produce partially sulfonated PPSU, as will be described in more detail below.

[0013] In the first method step, PPSU is introduced into sulfuric acid, for example, in the form of PPSU granules or powder. Here, at least a sufficient amount of PPSU is introduced into the sulfuric acid until the solubility limit of PPSU is reached, which can be identified based on sediment formation, turbidity, etc.

[0014] The introduction of PPSU into sulfuric acid can preferably be carried out with stirring at a temperature of 20°C to 120°C, preferably 40°C to 60°C. The preferred reaction time may be 3 to 24 hours, preferably 5 to 7 hours, and more preferably 6 hours. The pressure may be in the range of, for example, 0.1 bar to 100 bar, and may particularly correspond to atmospheric pressure. Optionally, the introduction of PPSU into sulfuric acid can be carried out under a protective gas atmosphere, for example, an argon atmosphere.

[0015] In a further step, undissolved components are separated from the reaction mixture, for example by filtration, to obtain the desired reagent as a liquid phase.

[0016] Through investigations by the inventors of the present invention, it was found that a portion of the PPSU introduced into sulfuric acid is highly functionalized by sulfonic acid groups and is therefore soluble. Consequently, the resulting reagent contains sulfuric acid and dissolved PPSU highly functionalized by sulfonic acid groups. The separated residue substantially contains unfunctionalized PPSU and partially functionalized PPSU.

[0017] The resulting reagent makes it possible to partially sulfonate PPSU in high yield; that is, subsequent sulfonation of PPSU using the obtained reagent is carried out with high selectivity for the partially functionalized product.

[0018] Further aspects of the present invention relate to a method for the partial sulfonation of polyphenylene sulfone, or a method for producing partially sulfonated polyphenylene sulfone.

[0019] The proposed method comprises the following steps: adding polyphenylene sulfone to the reactant prepared according to the method described above, and separating the partially sulfonated polyphenylene sulfone as an insoluble reaction product.

[0020] After adding polyphenylene sulfone to the reagent, functionalization of the polyphenylene sulfone by sulfonic acid groups occurs. With the use of the proposed reagent, this functionalization preferably results in partial functionalization, yielding partially sulfonated PPSU.

[0021] Subsequently, the partially sulfonated PPSU is separated from the liquid phase as an insoluble reaction product, for example, by centrifugation or filtration. After optional washing with water and / or ethanol, the partially sulfonated PPSU can be dried, for example, at 60°C for 12 hours. As a result, powdered partially sulfonated PPSU is obtained.

[0022] The liquid phase can be reused as a reactant for the partial sulfonation of polyphenylene sulfone, and for this purpose, it can be recycled, for example. This reduces the amount of sulfuric acid required, which is advantageous both for environmental protection and cost reasons.

[0023] The introduction of PPSU into the reactant can preferably be carried out with stirring at a temperature of 20°C to 120°C, preferably 40°C to 60°C. The preferred reaction time may be 3 to 24 hours, preferably 5 to 7 hours, and more preferably 6 hours. The pressure may be in the range of, for example, 0.1 bar to 100 bar, and may particularly correspond to atmospheric pressure. Optionally, the reaction may be carried out under a protective gas atmosphere, for example, an argon atmosphere.

[0024] Preferably, the proportion of PPSU can be 5% to 30% by weight, preferably 10% to 20% by weight. In other words, the addition of PPSU to the reactant can be carried out so that a composition having the specified weight proportion of PPSU is obtained immediately after the addition of PPSU.

[0025] The proposed method makes it possible to produce partially sulfonated PPSU in high yield, which has high chemical stability, heat resistance up to 160°C, and long-term stability, and can be used for the manufacture of membranes and / or electrodes for water electrolysis.

[0026] The obtained partially sulfonated PPSU is, for example, soluble in 1-methyl-2-pyrrolidone up to 25% by weight, and can be used in particular as a binder ionomer for PEM water electrolysis. Compared to sulfonated polyether ether ketone (PEEK), this material has particularly high stability against nucleophilic attack. It can be seen that the obtained partially sulfonated PPSU is stable over a period of more than 4 weeks in an O₂ atmosphere and an H₂ atmosphere at a temperature above 80°C, and is stable against OH radical attacks induced by storage in 10% by weight H₂O₂ under the same conditions.

[0027] In addition to improved environmental compatibility, partially sulfonated PPSU as an ionomer offers the potential to improve thermal, mechanical and / or chemical stability. The altered chemical structure compared to conventional PFAS also has the potential to solve further challenges related to long-term stability and gas transport (gas crossover).

[0028] A further aspect of the present invention relates to a further process for producing partially sulfonated polyphenylene sulfone.

[0029] This process envisages the total synthesis of partially sulfonated polyphenylene sulfone.

[0030] Total synthesis, also referred to as full synthesis, means that the partially sulfonated polyphenylene sulfone is produced entirely from simply constructed basic substances.

[0031] This method may, for example, involve reacting at least one hydroxyl component, such as a dihydroxyl component, with at least one halogen component, wherein at least one, preferably both, of the two components has one or more sulfonic acid groups and / or corresponding salts. Here, the hydroxyl component may be, for example, 4,4'-dihydroxy-(1,1'-biphenyl)-3-sulfonic acid or 4,4'-dihydroxydiphenylsulfone. The halogen component may be, for example, bis(halophenyl)sulfone, such as 2-fluoro-5-((4-fluorophenyl)sulfonyl)benzenesulfonic acid or 2-chloro-5-((4-chlorophenyl)sulfonyl)benzenesulfonic acid, or disodium-bis-(4-chloro-3-sulfophenyl)sulfone (CAS No. 51698-33-0). The use of bis(halophenyl)sulfone 2-fluoro-5-((4-fluorophenyl)sulfonyl)benzenesulfonic acid enables particularly high reaction rates. The use of multiple listed hydroxyl or halogen components is possible, thereby selectively influencing the properties of the reaction product.

[0032] Depending on the specific reactant, the reaction can be carried out under alkaline conditions, for example, by adding sodium hydroxide, potassium hydroxide, potassium carbonate, and / or sodium carbonate.

[0033] This is a polycondensation reaction. In the reaction of 4,4'-dihydroxy-(1,1'-biphenyl)-3-sulfonic acid with bis(halophenyl)sulfone 2-fluoro-5-((4-fluorophenyl)sulfonyl)benzenesulfonic acid, according to an unspecified reaction mechanism, in the first step, the sodium salt of the corresponding hydroxyl component is formed in situ by the reaction of 4,4'-dihydroxy-(1,1'-biphenyl)-3-sulfonic acid with sodium hydroxide. In the second step, actual polycondensation occurs between the sodium salt of the dihydroxyl component and the bis(halophenyl)sulfone, yielding partially sulfonated PPSU, where a sulfonic acid group is formed in the diphenylsulfone unit and a further sulfonic acid group is formed in the biphenyl unit.

[0034] The obtained partially sulfonated PPSU precipitates as sediment and can be separated by means of filtration, centrifugation, etc. After optional washing with water and / or ethanol, the partially sulfonated PPSU can be dried, for example, at 60°C for 12 hours. As a result, powdered partially sulfonated PPSU is obtained.

[0035] The polycondensation reaction can be carried out at temperatures ranging from 0°C to 285°C, for example. The pressure can be in the range of 0.1 bar to 100 bar, and may particularly correspond to atmospheric pressure. The ratio of the amount of hydroxyl component to the amount of halogen component can be in the range of 0.5 to 2, and particularly 1. It is conceivable to charge demineralized water to produce a solution of the hydroxyl component in a sulfolane-NaOH solution containing 10% to 50% by weight of NaOH, and a solution of the halogen component in a sulfolane-NaOH solution containing 10% to 50% by weight of NaOH. The solutions of the hydroxyl component and the halogen component can be added to water simultaneously with stirring. The concentrations of the hydroxyl component in the hydroxyl component solution and the halogen component in the halogen component solution can be in the range of 0.5 mol / l to 5 mol / l, for example.

[0036] In various modified forms, hydroxyl and halogen components, such as 4,4'-dihydroxy-(1,1'-biphenyl)-3-sulfonic acid and bis(halophenyl)sulfone, can be dissolved in sulfolane (tetrahydrothiophene-1,1-dioxide, CAS number 126-33-0), respectively, and used as sulfolane solutions. Sulfolane is characterized by its aprotic properties and high boiling point.

[0037] Optionally, this method may include stopping the reaction by adding a chain arrestor, such as chloromethane. This allows for adjusting the chain length within a range that enables industrial melt processing.

[0038] Similarly, further proposed methods for producing partially sulfonated polyphenylene sulfones enable the production of partially sulfonated PPSUs in high yield, which have high chemical stability and heat resistance and long-term stability, and can be used for the manufacture of membranes and / or electrodes for water electrolysis.

[0039] The obtained partially sulfonated PPSU is soluble in 1-methyl-2-pyrrolidone up to 25% by weight and can be used, in particular, as a binder ionomer and for fabricating membranes for PEM water electrolysis. Compared to sulfonated polyether ether ketone (PEEK), this material exhibits particularly high stability against nucleophilic attack. The obtained partially sulfonated PPSU is stable for more than 4 weeks at temperatures above 80°C in both O2 and H2 atmospheres and is stable against OH radical attack induced by storage in 10% by weight H2O2 under the same conditions.

[0040] A further aspect of the present invention relates to the use of a partially sulfonated polyphenylene sulfone produced by any of the methods described above for producing an electrode or membrane for carrying out water electrolysis.

[0041] The manufactured partially sulfonated PPSU is ionically conductive due to its sulfonic acid groups and can therefore be used as an ionomer. For example, it can be used as a so-called binder ionomer. Here, the term "binder ionomer" refers to the ability of the ionomer to function as a binder between the membrane and the catalyst, enabling stable bonding of the catalyst near the membrane. For example, the anode of a membrane electrode assembly (MEA) can be formed by applying a catalyst dispersed in a so-called binder ionomer to the membrane surface. Here, the membrane itself may also have partially sulfonated PPSU, or may consist of partially sulfonated PPSU manufactured according to the proposed method. Alternatively, other, preferably fluorine-free, ionomers can be used to manufacture the membrane.

[0042] In addition, a film having or consisting of a partially sulfonated PPSU manufactured according to the proposed method can be combined with another, preferably fluorine-free, ionomer as an electrode material.

[0043] Electrodes and membranes manufactured from partially sulfonated PPSU for water electrolysis are characterized by improved environmental compatibility. Therefore, they serve as a viable alternative when PFAS are prohibited. Furthermore, due to improved temperature stability, higher process temperatures can be selected for electrolysis. Additionally, these membranes are characterized by lower gas permeability, and therefore, electrolysis can be carried out with higher efficiency.

[0044] Further aspects of this invention relate to catalyst coating films for electrochemical cells, and more particularly, to a method for producing an electrolytic cell. The proposed method comprises the following steps: providing a solid partially sulfonated polyphenylene sulfone; dispersing the partially sulfonated polyphenylene sulfone in an anhydrous dispersion medium (water-free dispersion medium) to obtain a dispersion; mixing a catalyst material with the dispersion to form a catalyst paste; and applying the catalyst paste to a film substrate.

[0045] As the solid partially sulfonated PPSU, a partially sulfonated polyphenylene sulfone produced in accordance with the above description can be used, for example, in the form of a powder or granules.

[0046] A catalyst coating (CCM) has at least one porous electrode, which is realized by applying and bonding a catalytically active porous layer. Therefore, a catalyst coating can also be understood as a membrane electrode assembly (MEA).

[0047] This method includes, in the first step, providing a partially sulfonated PPSU in solid form, for example, in powder form, i.e., preferably in an undissolved or in-solution state.

[0048] This method further includes dispersing partially sulfonated PPSU in an anhydrous dispersion medium to obtain a dispersion.

[0049] The proportion of partially sulfonated polyphenylene sulfone in the dispersion can be, for example, 2% to 15% by weight. Such a proportion of partially sulfonated polyphenylene sulfone resulted in particularly good processability of the dispersion in the subsequent method steps.

[0050] The anhydrous dispersion medium can be selected from the group comprising, for example, dimethyl sulfoxide, N,N-dimethylformamide, N,N-diethylformamide, 2-pyrrolidone, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, N-methyl-2-pyrrolidone, and a mixture of N-ethyl-2-pyrrolidone, γ-butyrolactone, or diethylene glycol monoethyl ether in proportions selected from these.

[0051] It has been found that dispersants from the previously listed group, in their interaction with partially sulfonated PPSU, promote the formation of an intermediate layer ("intervening layer") as a functional layer for good long-term stability of the catalyst on the film substrate, i.e., material bonding can occur. This is achieved by selectively partially dissolving the surface of the film substrate more than water-based dispersants. This improves the electrochemical stability of the catalyst coating film and its high long-term stability when applied in electrochemical cells. By applying a mixture of dispersants, the adaptability during the production of the catalyst paste is further increased, thus enabling sufficiently high partial dissolution of the surface of the film substrate and tight material bonding in the intermediate layer region, depending on the coating system of the catalyst layer.

[0052] Dispersions of partially sulfonated PPSU in 1-methyl-2-pyrrolidone have been shown to be particularly stable over the long term. No gel formation was observed.

[0053] This method further includes, for example, thoroughly mixing a catalyst material in solid or powder form with a dispersion to form a catalyst paste.

[0054] The total proportion of the catalyst material and partially sulfonated polyphenylene sulfone in the catalyst paste can be 35% to 60% by weight, particularly 45% to 55% by weight. This allows for particularly good and uniform application of the catalyst paste to the film substrate in the subsequent method steps.

[0055] The catalyst material may include, for example, iridium, particularly solid or powdered iridium black, and / or platinum, particularly solid or powdered platinum black.

[0056] Iridium-containing catalyst materials can be used, in particular, as OER catalysts (Oxygen Evolution Reaction) for oxygen evolution reactions on the anode side. Alternatively, the anode catalyst material may contain IrOOH, IrO2, IrRuO2, and / or TiO2-supported, NbO2-supported, or SnO2-supported variants of the catalysts mentioned above, or corresponding material systems.

[0057] Platinum-containing catalyst materials can be used, in particular, as HER catalysts for hydrogen evolution reactions (HER reactions) at the cathode. Alternatively, they may also contain palladium, ruthenium, and / or carbon-supported variants / mixtures of the catalysts mentioned above.

[0058] In the formulation of catalyst pastes, the selection of dispersants is of paramount importance. In contrast to known coating methods, the application of anhydrous dispersion media for catalyst pastes has been proposed. In contrast to the previously common treatment of fluorine-free ionomers with water / alcohol mixtures based on methanol, ethanol, or isopropanol, the electrode compositions described herein produce a more stable "intervening layer," i.e., an intermediate or junctional layer between the film substrate and the electrode, thereby improving electrochemical stability and, consequently, extending the service life when applied in water electrolysis.

[0059] This method further includes, preferably, directly applying the catalyst paste to the corresponding film substrate (direct film coating). The catalyst paste described above can be used very advantageously in the direct film coating method. Herein, there is significantly greater applicability compared to the decal method, in which the catalyst layer is first deposited on a thermally stable support film, followed by the removal of the dispersant by heat, and the catalyst layer is transferred to a film under the action of pressure and temperature in a further process step.

[0060] The catalyst paste can be applied to the film substrate by, for example, doctor blade application, roll-to-roll application, slot nozzle coating, spraying, screen printing, and / or application rollers. Optionally, a vacuum plate can be used to hold the film substrate. The pressure during application can be, for example, in the range of 0.1 bar to 100 bar, and may particularly correspond to atmospheric pressure. The temperature during application can be, for example, in the range of 0°C to 100°C, and may particularly correspond to room temperature.

[0061] Optionally, this method may include, as a further process step, post-treatment of the film substrate coated with the catalyst paste by heat, for example, in an oven. The heat post-treatment can be carried out, for example, at a temperature of 110°C to 160°C for a period of 1 to 15 minutes. The heat post-treatment can improve the bonding of the catalyst layer to the film substrate, thereby contributing to even greater long-term stability. Furthermore, the heat post-treatment affects the formation of the electrode structure by influencing the volatilization rate and volume reduction of the dispersant.

[0062] The proposed method advantageously enables the cost-effective and easily scalable fabrication of large-area catalyst coatings for PEM water electrolysis.

[0063] In particular, the application of catalysts, whether as a so-called HER (hydrogen evolution reaction) for the hydrogen evolution reaction at the cathode or as an OER (oxygen evolution reaction) for the oxygen evolution reaction at the anode, can be significantly simplified and improved, thus enabling the use of fluorine-free catalyst-coated membranes (CCMs) based on partially sulfonated PPSU in HERs and OERs in electrolytic cells.

[0064] Furthermore, the proposed method enables the fabrication of fluorine-free films (CCMs) coated with catalytic materials on an industrial scale, for example, using roll-to-roll coating technology, and thus advantageously allows for faster processing times for corresponding components of electrolytic apparatus. Moreover, the presented method significantly improves both the ionic and mechanical bonding of catalytic materials to film substrates for fluorine-free film electrode assemblies (MEAs). Furthermore, the advantageous high material compatibility, the very good paste stability of the catalyst paste, the improved sedimentation behavior of this paste formulation, and the coating should be further emphasized. In addition, from a technical and economic standpoint, cumbersome pressing and post-processing methods are eliminated.

[0065] Further aspects of the present invention relate to catalyst-coated PEM film assemblies manufactured or that can be manufactured by the described method for producing catalyst-coated films.

[0066] A further aspect of the present invention relates to an electrolytic cell having a PEM film assembly.

[0067] A further aspect of the present invention relates to a cell stack having a plurality of such electrolytic cells, i.e., comprising a number of such electrolytic cells stacked and electrically connected in series. These form a cell stack or electrolytic stack that is expandable to accommodate a large electrolytic output.

[0068] A further aspect of the present invention relates to an electrolytic apparatus having such a cell stack.

[0069] The embodiments, features, and / or advantages relating here to the method may further relate to the manufactured product itself or the membrane assembly, as well as electrolytic cells, cell stacks, electrolytic equipment and / or entire Power-to-X power plants, and vice versa.

[0070] The expression "and / or" used here, when used with a set of two or more elements, means that each of the listed elements can be used individually, or any combination of two or more of the listed elements can be used.

[0071] The above-mentioned characteristics, features, and advantages of this invention, as well as the methods by which they are achieved, will be understood more clearly and distinctly in connection with the following description of embodiments, which are illustrated in more detail with reference to the figures. [Brief explanation of the drawing]

[0072] [Figure 1] The reaction scheme for the sulfonation of PPSU is shown. [Figure 2] The sequence scheme of a first exemplary method for producing partially sulfonated PPSU is shown. [Figure 3] A sequence scheme for a second exemplary method for producing partially sulfonated PPSU is shown. [Figure 4] This shows the reaction scheme for producing partially sulfonated PPSU by polycondensation. [Figure 5] The sequence scheme for the method of producing a catalyst coating film is shown. [Figure 6] A simplified schematic diagram of the catalyst coating film is shown. [Figure 7] The polarization curve of a membrane electrode assembly having partially sulfonated PPSU as the anode ionomer is shown. [Figure 8]This figure shows the long-term stability of a membrane electrode assembly having partially sulfonated PPSU as the anode ionomer.

[0073] Figure 1 shows the reaction scheme for the sulfonation of PPSU. When PPSU is reacted with sulfuric acid, for example at 60°C for 6 hours, sulfonation occurs, yielding a mixture of partially functionalized SPPSU or partially sulfonated PPSU1 and highly functionalized SPPSU. Partially sulfonated PPSU1 may have two sulfonic acid groups per repeating unit, for example, as shown on the left in Figure 1. Partially sulfonated PPSU1 is not water-soluble. Conversely, highly functionalized SPPSU has a higher degree of sulfonation, as shown on the right in Figure 1. Highly functionalized SPPSU is readily water-soluble and therefore unsuitable for further processing into films or application as a binder ionomer. Furthermore, highly functionalized SPPSU is highly sensitive to hydrolysis.

[0074] In contrast, investigations by the inventors of the present invention have shown that partially sulfonated PPSU1 is little to no water soluble, but is soluble in 1-methyl-2-pyrrolidone up to 25% by weight, making it suitable for use in membranes or as a binder ionomer. The number of sulfonic acid groups affecting ion exchange capacity is fewer in partially functionalized PPSU than in highly functionalized PPSU, and consequently, a lower ion exchange capacity may be expected. However, experiments by the inventors have shown that sufficient ion exchange capacity can be achieved, on the one hand, and significant improvements in heat resistance and chemical resistance can be achieved, along with higher long-term stability. As a result, partially sulfonated PPSU1 can be advantageously used in the large-scale industrial production of membranes and electrodes for water electrolysis.

[0075] In addition to the reaction products shown in Figure 1, further reaction products can be generated that differ in the number of sulfonic acid groups per repeating unit and / or the positions of the sulfonic acid groups.

[0076] Through investigations by the inventors of this invention, it was found that when the sulfonation reaction schematically shown in Figure 1 was carried out in concentrated sulfuric acid according to the prior art, only about 80% partially sulfonated PPSU and about 20% highly functionalized SPPSU were obtained. Therefore, the objective of this invention was to describe the possibility of increasing the yield of partially functionalized PPSU and / or an alternative synthetic route.

[0077] Figure 2 shows the sequence scheme of the first method for producing partially sulfonated PPSU. The entire procedure is divided into two sub-procedures 100 and 200, which can be performed immediately after each other or separately in time and / or space.

[0078] The first sub-procedure 100 serves to produce a reagent for the partial sulfonation of PPSU. In the first method step S1, 25 g of PPSU granules (Radel R-5000 NT) are added to 100 ml of 96% sulfuric acid while stirring and refluxing at 50°C under an argon atmosphere to obtain a saturated sulfuric acid solution. After 6 hours of reaction, in method step S2, all undissolved components are separated and discarded. The resulting liquid phase is then used as a reagent for the production of partially sulfonated PPSU1 in the second sub-procedure 200.

[0079] In step S3 of the method, 100 ml of the obtained reagent is pre-charged into a 250 ml three-necked round-bottom flask equipped with a KPG stirrer and reflux condenser. Under an argon atmosphere, 25 g of PPSU granules (Radel R-5000 NT) are introduced into the reagent while stirring and reflux cooling, and the mixture is functionalized at 50°C for 6 hours.

[0080] In step S4 of the method, the partially sulfonated PPSU1 is separated by filtration as an insoluble reaction product.

[0081] In step S5 of the method, the separated reaction product is rapidly washed to neutral with Nutsche, and then, in step S6 of the method, it is dried at 60°C for 12 hours. By using the pre-prepared reagent, the yield of partially sulfonated PPSU1 was increased to over 90% compared to functionalization without the reagent.

[0082] Subsequently, the partially functionalized PPSU can be further processed as described below, with reference to Figure 5.

[0083] Figure 3 shows a sequence scheme of examples of further method 300 for producing partially sulfonated PPSU.

[0084] In step S10 of the method, 2-fluoro-5-((4-fluorophenyl)sulfonyl)benzenesulfonic acid is dissolved in a sodium sulfolane hydroxide solution containing 30% by weight of sodium hydroxide while stirring at room temperature.

[0085] In step S11 of the method, 4,4'-dihydroxy-(1,1'-biphenyl)-3-sulfonic acid is dissolved in a sodium sulfolane hydroxide solution containing 30% by weight of sodium hydroxide while stirring at room temperature.

[0086] In step S12 of the method, 100 ml of distilled water is placed in a 2 L three-necked round-bottom flask equipped with an argon purge and a KPG stirrer, and the temperature is adjusted to T = 90°C.

[0087] In step S13, both sulfolane solutions are metered and supplied at a rate of 100 ml / min using a hose pump. After both solutions have been completely added, the mixture is stirred under argon purging at 90°C for 1.5 hours so that all the reactants can react in step S14. The flask is then cooled to room temperature while being stirred under argon purging in step S15.

[0088] Subsequently, in step S16, the mixture is heated again to 90°C for 5 minutes, and then cooled to room temperature (step S17). Since a kind of nucleation resulting in almost complete precipitation can be observed, the cooling in step S15, combined with the reheating in step S16, yields a higher yield.

[0089] In step S18 of the method, the formed deposit is separated by centrifugation and then washed three times with 500 ml of water and twice with 200 ml of ethanol (step S19 of the method). The residue, which is partially sulfonated PPSU1, is dried at 60°C for 12 hours (step S20 of the method).

[0090] Figure 4 shows a simplified diagram of the reaction scheme of the polycondensation reaction that forms the basis of Method 300. The reaction product is partially sulfonated PPSU1, which, in particular, has one sulfonic acid group in the diphenyl sulfone unit and further sulfonic acid groups in the biphenyl unit. The proposed Method 300 allows for the introduction of a defined number of active groups, i.e., chemical groups that contribute to ion exchange capacity. Since an unintended or statistical distribution of sulfonic acid groups can undesirably increase solubility in water, this product, which can be well defined based on the total synthesis, allows for increased chemical stability. Subsequently, the partially functionalized PPSU can be further processed as described below with reference to Figure 5.

[0091] Figure 5 shows a sequence scheme of an exemplary method 400 for producing a catalyst coating film 10 for an electrochemical cell, in this case an electrolytic cell for water electrolysis.

[0092] After the start, Method 400 includes, in step S50, first providing partially sulfonated polyphenylene sulfone 1 as a starting material in solid form. For this purpose, in one embodiment, partially sulfonated PPSU1 obtained by Methods 100, 200, which were previously described with reference to Figure 2, is used to produce partially sulfonated polyphenylene sulfone 1. Alternatively, for this purpose, partially sulfonated PPSU1 obtained by Method 300, which were previously described with reference to Figure 3, can be used, for example, to produce partially sulfonated polyphenylene sulfone 1.

[0093] Method 400 further includes, in step S51, dispersing partially sulfonated PPSU1 in an anhydrous dispersion medium to form a dispersion. In one embodiment, N-methyl-2-pyrrolidone is used as the anhydrous dispersion medium. The proportion of partially sulfonated PPSU1 in the dispersion is 15% by weight. Alternatively, other anhydrous dispersion mediums can be used. The proportion of partially sulfonated PPSU1 can be adjusted to suit the dispersant, for example, its viscosity.

[0094] In step S52 of the method, the dispersion is thoroughly mixed with catalyst material 2. In this example, metallic iridium (black) was used as catalyst material 2. From step S52 of this method, a paste-like, generally viscous or highly viscous coating material is obtained, thereby forming a catalyst paste. Here, the catalyst paste is adjusted so that it has a high solid content overall of catalyst material 2 and partially sulfonated PPSU1. In one example, this solid content was between 40% and 60% by weight, preferably 50% by weight.

[0095] In step S53 of the method, the catalyst paste is directly applied to the film substrate 4. Preferably, the film substrate 4 can be made of a fluorine-free polymer. When applying the catalyst paste to the film substrate 4, a direct coating method is applied. In one embodiment, the application is performed by a doctor blade, but other direct coating methods are also available. The use of a direct coating method makes it possible to produce large fluorine-free catalyst coated films 10 in a cost-effective and scalable manner.

[0096] After applying the catalyst paste to the film substrate 4, a heat post-treatment (method step S54) is performed. In one embodiment, the heat post-treatment includes pre-drying at 80°C for 4 hours, followed by curing by heating at 140°C for 5 to 10 minutes, and optionally up to 20 minutes. In this way, a good surface structure of the catalytically active porous layer and uniform bonding with long-term stability to the film substrate are obtained.

[0097] The proposed method involves intentionally and sufficiently partially dissolving the film substrate 4, particularly in the boundary region with the coated layer having the catalyst material 2, thereby forming a characteristic intermediate layer 5 (see Figure 6) ("interlayer") as an important functional layer. Thus, the partially sulfonated PPSU 1 functions not only as an ionomer but also, advantageously, simultaneously as a binder or adhesive for the catalyst material 2. Here, it was found that selecting an anhydrous dispersion medium to produce the catalyst paste facilitates this dissolution process in the boundary layer and the formation of the intermediate layer 5.

[0098] Figure 6 shows a simplified diagram of the catalyst coating film 10. The selected composition and application method of the catalyst paste selectively initiate a partial dissolution process, which, through the selection of the dispersant and the properties of the partially sulfonated PPSU1, leads to the formation of an intermediate layer 5, a crucial functional layer in the manufacturing process. This intermediate layer 5 provides good adhesion and long-term stability of the catalyst layer 3, which has the catalyst material 2 and the partially sulfonated PPSU1, to the film substrate 4.

[0099] The intermediate layer 5 has a layer thickness D of approximately 3 to 10 μm, and therefore, a strong, long-term stable material bond between the catalyst layer 3 and the film substrate 4 is formed by the partial dissolution of similar ionomers.

[0100] A catalyst layer 3 provides electrodes on the film substrate 4. In the partially enlarged view of Figure 8, an anode electrode having iridium (Ir) as the catalyst material 2 is provided. Similarly, on the opposite side of the film substrate 4, a cathode electrode having platinum (Pt) as the catalyst material 2 is formed. Here, the microstructure of the electrodes is an ionomer, i.e., a three-dimensional network of partially sulfonated PPSU 1, catalyst material 2, and pores. Due to the porous structure, the electrodes are permeable to the transport of reactants and electrolysis products.

[0101] In one example, an ion exchange capacity of 0.031 mmol / g was measured for the ionomer in the anode electrode.

[0102] The present invention makes it possible to manufacture fluorine-free catalyst coatings for PEM water electrolysis on an industrial scale using partially sulfonated PPSU as a binder ionomer. This addresses the impending PFSA ban across Europe. The catalyst coating 10 is proven to be long-term stable and thus efficient with respect to the water electrolysis that can be implemented, as demonstrated below based on Figures 7 and 8 and the accompanying description.

[0103] Figure 7 illustrates the electrochemical properties of the catalyst coating film 10 or film electrode assembly of the example, based on polarization curves (UI characteristic curves plotting the cell voltage U against each current density I). Polarization curves were recorded after 24, 120, and 192 hours of operation at a temperature of 60°C and ambient pressure.

[0104] All three curves closely match, indicating that the voltage increases uniformly with increasing current density. Therefore, the film electrode assembly of the example has good electrochemical performance.

[0105] Figure 8 shows the change in cell voltage U over time as evidence of the long-term stability of the film electrode assembly in the example. From the start of measurement to approximately 24 hours after the start of measurement, the voltage was 1 A / cm². 2Note that the applied current density resulted in a voltage of approximately 1.8V. After 24 hours, the first polarization curve was recorded (see Figure 7, 24-hour curve), at which point the measurement had to be interrupted, which is recognizable based on the sharp voltage drop, as shown in Figure 8.

[0106] After recording the first polarization curve, 2 A / cm 2 An increased current density was applied, resulting in a voltage of approximately 2.0. After 120 hours, the measurement was interrupted again to allow for the recording of further polarization curves (see Figure 7, 120-hour curve). Subsequently, 2 A / cm 2 The current density was applied again. The measured voltage was again approximately 2V. After 192 hours, the process was interrupted again and a third polarization curve was recorded (Figure 7, 192-hour curve). After recording the third polarization curve, the measurement was changed to 2A / cm². 2 The current density continued. The constant voltage throughout the entire time is evidence of very good long-term stability of the film electrode assembly. In contrast, degradation may become recognizable based on the voltage increase at a constant current density, which could be due to various degradation causes, such as catalyst passivation, poor contact between components, or ionomer degradation.

[0107] Although the present invention has been illustrated and described in more detail by preferred embodiments, the present invention is not limited to the disclosed examples, and those skilled in the art can derive other modifications therefrom without departing from the scope of protection of the present invention.

[0108] The present invention relates to a method 100 for producing a reagent for the partial sulfonation of polyphenylene sulfone, comprising the steps: S1: introducing polyphenylene sulfone into sulfuric acid to at least its solubility limit and S2: separating undissolved components to obtain the reagent. The present invention further relates to a method for producing a partially sulfonated polyphenylene sulfone 1, a method 400 for producing a catalyst coating film 10 for an electrochemical cell, and a PEM film assembly having the catalyst coating film 10. [Explanation of symbols]

[0109] 1...Partially sulfonated polyphenylene sulfone, 2...Catalyst material, 3...Catalyst layer, 4...Membrane substrate, 5...Intermediate layer, 10...Catalyst coating film

Claims

1. A method (100) for producing a reagent for the partial sulfonation of polyphenylene sulfone, comprising the following steps: - S1: A step of introducing polyphenylene sulfone into sulfuric acid to at least the solubility limit, and - S2: Step of separating undissolved components to obtain a reactant. A method (100) having the following characteristics.

2. A method (200) for producing a partially sulfonated polyphenylene sulfone (1), comprising the following steps: -S3: Adding polyphenylene sulfone to a reagent prepared according to the method (100) of claim 1, and - S4: A step to separate the partially sulfonated polyphenylene sulfone (1) as an insoluble reaction product. A method (200) having the following characteristics.

3. The proportion of polyphenylene sulfone in the reagent is 5% to 30% by weight. The method according to claim 2 (200).

4. A method (300) for producing a partially sulfonated polyphenylene sulfone (1) by total synthesis, - S14: A step of reacting at least one hydroxyl component with at least one halogen component, wherein the hydroxyl component is 4,4'-dihydroxy-(1,1'-biphenyl)-3-sulfonic acid or 4,4'-dihydroxydiphenyl sulfone. A method (300) having the following characteristics.

5. The halogen component is bis(halophenyl)sulfone or disodium-bis-(4-chloro-3-sulfophenyl)sulfone. The method according to claim 4.

6. - S10, S11: Steps to dissolve the hydroxyl component and the halogen component in sulfolane. The method according to claim 4 or 5 (300), having the following characteristics.

7. Use of a partially sulfonated polyphenylene sulfone (1) produced by the method (200, 300) of any one of claims 2 to 6 for producing an electrode or membrane for carrying out water electrolysis.

8. A method (400) for producing a catalyst coating film (10) for an electrochemical cell, comprising the following steps: - S50: A step of providing a solid partially sulfonated polyphenylene sulfone (1), - S51: A step of dispersing the partially sulfonated polyphenylene sulfone (1) in an anhydrous dispersion medium to obtain a dispersion, - S52: A step of mixing the catalyst material (2) with the dispersion to make a catalyst paste, and - S53: Step of applying the catalyst paste to the film substrate (4) A method (400) having the following characteristics.

9. - S54: A step of post-treating the film substrate (4) to which the catalyst paste has been applied by heat. The method according to claim 8 (400), having the following characteristics.

10. The method according to claim 8 or 9 (400), wherein the partially sulfonated polyphenylene sulfone (1) is a partially sulfonated polyphenylene sulfone (1) produced according to the method according to any one of claims 2 to 7 (200, 300).

11. A PEM film assembly having a catalyst coating film (10) manufactured according to the method (400) described in any one of claims 8 to 10.

12. An electrolytic cell comprising the PEM film assembly described in claim 11.

13. A cell laminate comprising a plurality of electrolytic cells according to claim 12.

14. An electrolytic apparatus having the cell laminate described in claim 13.